Spatial distribution of diabetic capillary non‐perfusion. (6th July 2021) - Falavarjani, Khalil Ghasemi; Mirshahi, Reza; Riazi‐Esfahani, Hamid; Anvari, Pasha; Habibi, Abbas; Ashraf Khorasani, Maryam; Shad, Esrafil
Abstract: Objective: To evaluate the distribution of capillary non‐perfusion (CNP) in superficial and deep capillary plexuses (SCP and DCP) in eyes with diabetic retinopathy (DR). Methods: In this retrospective case series, macular optical coherence tomography angiography (OCTA) images were obtained from eyes with DR without diabetic macular edema (DME). The area of CNP in SCP and DCP was delineated using an automated approach after excluding the foveal avascular zone (FAZ) and major retinal vessels. The distribution and spatial correlation of the CNP in each layer were analyzed. Results: Forty‐three eyes of 27 patients with DR with a mean age of 59.10 ± 9.05 years were included. The mean CNP area in SCP was statistically significantly higher than DCP (0.722 ± 0.437 mm 2 vs. 0.184 ± 0.145 mm 2, respectively, p < .001). There was a statistically significant association between mean BCVA (0.28 ± 0.21 logMAR) and CNP area in DCP ( p = .01). After automated subtraction of CNP areas in DCP from SCP, 25.43 ± 15.05% of CNP areas in the DCP had co‐localized CNP areas in SCP. The CNP percentage was statistically significantly different between the concentric rings on foveal center, both in SCP and in DCP (both p < .001) showing a decreasing trend from the outer ring toward the center. Conclusion: In DR, SCP is more ischemic than DCP. This is in contrast to the previously described oxygenation‐dependent ischemic cascade following acute retinal vascular occlusions. This study provides further insight into the retinal ischemia in DR.